The Acute Effect of Sodium Chloride on the Zooplankton Crustaceans Daphnia pulex (Crustacea: Cladocera) - Bassat, S.F.; Al-Azawi, Z.N. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The present study included the effect of acute exposure of different concentrations of sodium chloride on the Zooplankton Crustacean Daphnia pulex which belong to the order Cladocera. The lethal concentrations killing 50% of the population (LC50) after 24hrs and 48hrs were 2.95â€° and 2.63â€° respectively While lethal concentrations killing 100%  of the population (LC100) and non lethal concentrations (LC0) were 6â€° and 0.5â€° after 24hrs of exposure to NaCl. The acute exposure of the Crustacean Daphnia pulex showed increasing in mortality percentages with increasing the concentrations and exposure time